Association of Genes in the NF-kappa B Pathway with Antibody-Positive Primary Sjogren's Syndrome - Nordmark, Gunnel; Wang, Chuan; Vasaitis, Lilian; Eriksson, Per; Theander, Elke; Kvarnstrom, Marika; Forsblad-d'Elia, Helena; Jazebi, Helmi; Sjowall, Christopher; Reksten, Tove Ragna; Brun, Johan G.; Jonsson, Malin V.; et al. (Scandinavian Journal of Immunology, 2013)
Primary Sjogren's syndrome (SS) is a systemic autoimmune inflammatory disease characterized by focal lymphocytic infiltrates in the lachrymal and salivary glands and autoantibodies against the SSA/Ro and SSB/La antigens. Experimental studies have shown an activation of NF-B in primary SS. NF-B activation results in inflammation and autoimmunity and is regulated by inhibitory and activating proteins. Genetic studies have shown an association between multiple autoimmune diseases and TNFAIP3 (A20) and TNIP1 (ABIN1), both repressors of NF-B and of IKBKE (IKK epsilon), which is an NF-B activator. The aim of this study was to analyse single nucleotide polymorphisms (SNPs) in the IKBKE, NFKB1, TNIP1 and TNFAIP3 genes for association with primary SS. A total of 12 SNPs were genotyped in 1105 patients from Scandinavia (Sweden and Norway, n=684) and the UK (n=421) and 4460 controls (Scandinavia, n=1662, UK, n=2798). When patients were stratified for the presence of anti-SSA and/or anti-SSB antibodies (n=868), case-control meta-analysis found an association between antibody-positive primary SS and two SNPs in TNIP1 (P=3.4x10(-5), OR=1.33, 95%CI: 1.16-1.52 for rs3792783 and P=1.3x10(-3), OR=1.21, 95%CI: 1.08-1.36 for rs7708392). A TNIP1 risk haplotype was associated with antibody-positive primary SS (P=5.7x10(-3), OR=1.47, 95%CI: 1.12-1.92). There were no significant associations with IKBKE, NFKB1 or TNFAIP3 in the meta-analysis of the Scandinavian and UK cohorts. We conclude that polymorphisms in TNIP1 are associated with antibody-positive primary SS.